Membranous and cartilaginous vocal fold adduction in singing - Herbst, Christian T; Qiu, Qingjun; Schutte, Harm K; Švec, Jan G (The Journal of the Acoustical Society of America, 2011)
While vocal fold adduction is an important parameter in speech, relatively little has been known on the adjustment of the vocal fold adduction in singing. This study investigates the possibility of separate adjustments of cartilaginous and membranous vocal fold adduction in singing. Six female and seven male subjects, singers and non-singers, were asked to imitate an instructor in producing four phonation types: "aBducted falsetto" (FaB), "aDducted falsetto" (FaD), "aBducted Chest" (CaB), and "aDducted Chest" (CaD). The phonations were evaluated using videostroboscopy, videokymography (VKG), electroglottography (EGG), and audio recordings. All the subjects showed less posterior (cartilaginous) vocal fold adduction in phonation types FaB and CaB than in FaD and CaD, and less membranous vocal fold adduction (smaller closed quotient) in FaB and FaD than in CaB and CaD. The findings indicate that the exercises enabled the singers to separately manipulate (a) cartilaginous adduction and (b) membranous medialization of the glottis though vocal fold bulging. Membranous adduction (monitored via videokymographic closed quotient) was influenced by both membranous medialization and cartilaginous adduction. Individual control over these types of vocal fold adjustments allows singers to create different vocal timbres.
Keywords: hlasové řasy; Female; Glottis; Music; glottis; hudba; ženské pohlaví; lidé; Vocal Cords; Laryngeal Cartilages; laryngeální chrupavky; Membranes; Male; Phonation; fonace; mužské pohlaví; Voice Quality; kvalita hlasu; membrány; Humans